Exploring mechanical characteristics of recycled concrete aggregates from demolition waste: advancements, challenges, and future directions for sustainable construction: a review - Arnab Mandal; Amit Shiuly (Discover Civil Engineering)
Abstract The escalating demand for construction materials and the imperative of waste reduction have spurred interest in utilizing recycled concrete from demolition waste as a sustainable alternative. This comprehensive review delves into the utilization of recycled concrete from demolition waste as a sustainable alternative in construction practices, addressing the escalating demand for construction materials and the imperative of waste reduction. It explores the technological advancements, environmental benefits, and economic considerations associated with recycled concrete, examining methodologies for recycling aggregates and evaluating their physical, chemical, and durability properties in comparison to traditional concrete. Additionally, the review discusses the role of recycled concrete in advancing sustainable development goals, highlighting current challenges and proposing strategies for widespread adoption. Future research directions are outlined, emphasizing the need for effective pre-processing treatments, exploration of synergistic effects of multiple recycled aggregates, development of proper classification systems, and investigation of applications in Geo-polymer concrete. The review concludes with insights into the mechanical properties of recycled concrete and the influence of pre-processing techniques on recycled fine aggregates, offering valuable guidance for researchers, practitioners, policymakers, and stakeholders invested in the sustainable future of the construction industry.